In-vitro tests for the biocontrol of Rhipicephalus microplus with entomopathogenic fungi in Uruguay - Olhagaray, Ernestina (2022)
The common cattle tick, Rhipicephalus microplus, generates millionaire losses in the livestock industry worldwide (US$18 billion/year). In addition to its direct pathogenic effects, as anemia and low production, it´s also the vector of Babesia bigemina, B.bovis and Anaplasma marginale, agents that cause babesiosis and anaplasmosis, which often leads to the death of animals. Control with chemical products has been difficult in recent decades due to the development of resistance, residues in animal products and subproducts and environmental contamination. In Uruguay, acaricide resistance is widely dispersed, and multi-resistant populations have been diagnosed complicating its control, therefore, alternative methods are being thought.